2018
DOI: 10.3389/fphar.2018.01071
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitacin B Induces Hypoglycemic Effect in Diabetic Mice by Regulation of AMP-Activated Protein Kinase Alpha and Glucagon-Like Peptide-1 via Bitter Taste Receptor Signaling

Abstract: Taste receptors exist in several organs from tongue to colon and have diverse functions dependent on specific cell type. In enteroendocrine L-cells, stimulation of taste receptor signaling induces incretin hormones. Among incretin hormones, glucagon-like peptide-1 (GLP-1) induces insulinotropic action by activating GLP-1 receptor of pancreatic β-cells. However, GLP-1 mimetic medicines have reported clinical side effects, such as autoimmune hepatitis, acute kidney injury, pancreatitis, and pancreatic cancer. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 56 publications
0
33
0
Order By: Relevance
“…Cuc-B induces hypoglycemic effect in diabetic mice via bitter taste receptor signaling at enteroendocrine L-cells in mice ( Kim et al, 2018 ). Hemolymph glucose levels in control and Gr33a 1 mutant male flies fed with cuc-B and caffeine were measured to assess the capacity of these compounds to alleviate hyperglycemia in Drosophila ( Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cuc-B induces hypoglycemic effect in diabetic mice via bitter taste receptor signaling at enteroendocrine L-cells in mice ( Kim et al, 2018 ). Hemolymph glucose levels in control and Gr33a 1 mutant male flies fed with cuc-B and caffeine were measured to assess the capacity of these compounds to alleviate hyperglycemia in Drosophila ( Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we demonstrated that the regulation of hemolymph glucose levels depended on how much cuc-B-treated food was consumed by the flies. Given that the Gr33a-GAL4 reporter is known to be expressed in the intestine and midgut enteroendocrine cells ( Park and Kwon, 2011 ), including the peripheral neurons of the labellum and legs, hyperglycemia suppression might be positively controlled by bitter taste receptors in the intestinal cells similar to mice ( Kim et al, 2018 ). However, there are several arguments against this explanation.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is important to emphasize that this is not the sole promising novel drug class. This is indicated by findings from the research on the first-in-class drug, an adenosine monophosphate (AMP)-activated protein kinase activator, targeting one of the key players in the process of energy balance preservation, especially during caloric disturbances[113], and, finally, findings on the first monoclonal antibody, bimagrumab, that blocks the myostatin type II receptor, which results in fat reduction[114].…”
Section: Resultsmentioning
confidence: 99%
“…Although less well studied, cucumber acts as an antioxidant on insulin resistance and its related diseases 22-24 . Cucurbitacin B, a natural compound that exists in edible plants (bitter melons, cucumbers, pumpkins and zucchini), has anti-inflammatory and hypoglycemic properties through the activation of Nrf2 25,26 . These results and those of the recent study on fermented foods suggest a strong link between Nrf2 and the protection against severe forms of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…properties through the activation of Nrf2 25,26 . These results and those of the recent study on fermented foods suggest a strong link between Nrf2 and the protection against severe forms of COVID-19.…”
mentioning
confidence: 99%